2022
DOI: 10.2147/jir.s344009
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Serum IGF-1 and Leptin as Biomarkers: Towards Screening for and Diagnosing Postmenopausal Osteoporosis

Abstract: Purpose To investigate the differences of several serum markers among population with different bone mass and to explore the utility of new potential biomarker for the diagnosing and screening for postmenopausal osteoporosis (PMOP). Materials and Methods A total of 1055 postmenopausal women were screened and gathered data on BMD screening, biological samples, and questionnaire information. A liquid chip assay was used to measure serum IL-6, IGF-1, BMP-2, VEGF, leptin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 28 publications
1
13
0
1
Order By: Relevance
“…Human studies have confirmed that leptin-VEGF crosstalk is genderspecific. [125][126][127][128][129][130][131][132][133][134][135][136] In subjects with obesity, leptin-VEGF crosstalk is strongly associated with oncogenesis and chemoresistance. 109,110 It can be stated that the leptin-VEGF crosstalk in patients with excess body mass, obesity-related disorders, and increased CVR urgently needs further scientific investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human studies have confirmed that leptin-VEGF crosstalk is genderspecific. [125][126][127][128][129][130][131][132][133][134][135][136] In subjects with obesity, leptin-VEGF crosstalk is strongly associated with oncogenesis and chemoresistance. 109,110 It can be stated that the leptin-VEGF crosstalk in patients with excess body mass, obesity-related disorders, and increased CVR urgently needs further scientific investigation.…”
Section: Discussionmentioning
confidence: 99%
“…132 Comparing borderline overweight postmenopausal osteoporotic women with overweight non osteoporotic controls, Zhang et al found that the osteoporotic women had lower serum leptin and insulin-like growth factor 1 levels, which additionally presented positive correlations with each other, with no differences in VEGF. 133 In premenopausal and postmenopausal women, Morad et al found that VEGF and leptin in breast tissue correlated and that dietary flaxseed affected adipokine levels in the breast. 134 In postmenopausal women, aerobic training lowered serum leptin, interleukin 8 (IL-8), TNF-α, and resistin levels with no effect on VEGF level.…”
Section: Human Studiesmentioning
confidence: 99%
“…From 2017 to 2020, we conducted the community-based OP and associated fractures screening in the Beijing area (BEYOND study) in order to explore the prevalence of disease, risk factors, and the characteristics of related biomarkers (6,7). In this study, we found that leptin appears to be a key biomarker associated with PMOP and in combination with other indicators can predict the occurrence of PMOP, suggesting a potential association between lipid metabolismrelated indicators and OP (8). Given the worldwide increased body mass index (BMI) and exponentially growing obesity rate, understanding the risk of osteoporosis in the DL population has never been more important (9).…”
Section: Introductionmentioning
confidence: 92%
“…Ayrıca bağırsak mikrobiyotasının, duygu durumunun regülasyonunda, hormonların üretiminde ve hormon salınımın düzenlenmesinde etkisi vardır. Yapılan bazı çalışmalarda bağırsak mikrobiyomu, obezite, otizm ve multipl skleroz ile de ilişkilendirilmiştir (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28).…”
Section: Mikrobiyotaunclassified